THE INFLUENCE OF ISLAMIC BOARDING SCHOOL CULTURE AND VISIONARY LEADERSHIP STYLE ON THE QUALITY OF ISLAMIC BOARDING SCHOOL EDUCATION SERVICES IN EAST JAKARTA - MUTTAQIN, Zaenul; PRIYONO, Dwi; FUAD, Ai Fatimah Nur (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2024)
The aim of this research is to analyze, test and obtain a clear picture of the influence of situational leadership and work climate on the quality of academic services in kindergartens in Larangan District, Tangerang City. This research uses a quantitative approach and hypothesis testing uses the path analysis method, while the data collection technique uses questionnaires, with a sample of 200 teachers from a population of 250 kindergarten teachers in Larangan District, Tangerang City. Based on the results of hypothesis testing from the research discussion, several conclusions can be put forward as follows: (1) There is a direct positive influence of situational leadership on the quality of academic services in kindergartens throughout Larangan District, Tangerang City. (2) There is a positive and significant direct influence of work climate on the quality of academic services in kindergartens in Larangan District, Tangerang City. (3) There is a direct positive and significant influence of situational leadership on the work climate in kindergartens in Larangan District, Tangerang City.